Sobre las posibilidades de la crítica: Foucault y la flecha apuntada hacia el corazón de la actualidad (2014)
In our present of transition it seems to be a fairly widespread consensus on the need to develop ways of critical thinking. However, this consensus is not replicated with regard to the particular characteristics that the exercise of critical thinking could ever take. In order to outline some coordinates that will help us to think the conditions and possibilities of critical thinking nowadays, this article will review the considerations proposed by Michel Foucault on the exercise of criticism understood as a historical-philosophical practice that implies a commitment to current time. Also, this article will establish some specific comparisons with other meanings of the criticism in pursuit to add specificity to this review. Finally, we propose some epistemic and ethical-political considerations regarding the presented results.